Henoch-Schönlein purpura with epididymo-orchitis: A rare extra-cutaneous manifestation - Majd Oweidat; Islam H. Karajeh; Widad Abu Mayyala; Mohammed Alra'e; Ammar Y. Hmidat (Urology Case Reports)
Henoch-Schönlein Purpura (HSP), or IgA vasculitis, is a systemic inflammatory disorder primarily affecting children. While common symptoms include purpura, abdominal pain, and arthritis, testicular involvement is rare. We report a case of a young boy presenting with severe scrotal pain and swelling, later identified as epididymo-orchitis secondary to HSP. Diagnosis was confirmed via Doppler ultrasound, and treatment with corticosteroids and antibiotics resulted in rapid symptom resolution. This case highlights the importance of recognizing rare extra-cutaneous manifestations of HSP and underscores the need for prompt diagnosis and tailored management to achieve favorable outcomes.